Priorities for Future Research About Screen Use and Adolescent Mental Health: A Participatory Prioritization Study - Vera San Juan, Norha; Oram, Sian; Pinfold, Vanessa; Temple, Rachel; Foye, Una; Simpson, Alan; Johnson, Sonia; Hardt, Selina; Abdinasir, Kadra; Edbrooke-Childs, Julian (Frontiers in Psychiatry, 2022)
Introduction: As screen use increases, so has interest in its impact on young people’s mental health. Evidence to inform policy development is lacking, and to date research agendas have been driven mainly by researchers and technology developers. This study aimed to identify research priorities for future research on screen use and adolescent mental health, from the perspectives of young people, parents/carers, and teachers. Methods: The study design was informed by the James Lind Alliance Priority Setting Partnership approach. A three-stage consensus-based process of consultation to identify research priorities using qualitative and quantitative methods. Research was guided by a steering group comprising researchers, third sector partners, clinicians, parents/carers and young people. A Young People’s Advisory Group contributed at each stage. Results: Initial steps generated 26 research questions of importance to children and young people; these were ranked by 357 participants (229 children and young people and 128 adults). Consensus was reached for the prioritization of four topics for future research: (i) the impact of exposure to adult content on young people’s mental health and relationships; (ii) the relationship between screen use and the wellbeing of young people from vulnerable groups; (iii) the impact of screen use on brain development; and (iv) the relationship between screen use and sleep. Additionally, young participants prioritized questions about online bullying, advertisements targeting young people, and the relationship between social media and specific mental health conditions. Research topics of interest arising specifically during the pandemic included the effects on adolescent mental health of exposure to constant news updates and online racial bias, and how young people take part in activism online Conclusion: These findings will enable researchers and funders to conduct research that is needs-oriented and relevant to the target audience.